ANALYSIS AND MATHEMATICAL MODELING OF THE ENERGY CONSUMPTION OF LINTERING MACHINES IN COTTON CLEANING FACTORIES - Tukhtamishev Botir Kunishevich, (International Journal of Innovations in Engineering Research and Technology, 2026)
Estimating energy consumption in the processing of cotton raw materials in a linter, determining the patterns of changes in electrical loads and relative energy consumption and the most favorable modes. Also, it is important to correctly determine the installed power of the electric drives of linter machines and determine the required power on the shaft of their motors, and analyze the energy performance of the enterprise and workshops.